Politics of Power and Authoritarianism: An Analysis of Government Dynamics in the Middle East - Hanna, Amida; Basri, Seta; Kurniawan, Nanang (PINISI Discretion Review, 2024)
The political landscape of the Middle East is marked by complex power dynamics, where authoritarianism has historically shaped government structures and influenced societal developments. This study aims to explore the intricate relationships between power, governance, and authoritarianism in various Middle Eastern nations. By focusing on the historical and contemporary manifestations of political authority, this research seeks to understand the strategies employed by ruling elites to maintain control, as well as the impact on political stability and citizen participation. A qualitative research methodology is utilized, involving in-depth case studies, document analysis, and interviews with political analysts and scholars specializing in Middle Eastern politics. The data gathered is analyzed using thematic analysis to uncover patterns of governance and authoritarian practices. The findings indicate that the concentration of power in the hands of a few elites, combined with limited political pluralism and restricted civic freedoms, perpetuates a cycle of authoritarian governance. Furthermore, the study highlights the role of external actors in either reinforcing or challenging these regimes. The research contributes to a deeper understanding of the resilience of authoritarianism in the region and offers insights into potential pathways for political reform.